Perception: A Blind Spot in Brandom's Normative Pragmatics - Kalpokas, Daniel Enrique (2019)
Brandom explains perceptual knowledge as the product of two distinguishable sorts of capacities: (i) the capacity to reliably discriminate behaviorally between different sorts of stimuli; and (ii) the capacity to take up a position in the game of giving and asking for reasons. However, in focusing exclusively on the entitlement of observation reports, rather than on perception itself, Brandom passes over a conception of perceptual experience as a sort of contentful mental state. In this article, I argue that this is a blind spot, which makes Brandom's account of perceptual knowledge unable to properly accommodate the phenomenon of seeing aspects and to explain how we can justify the attributions of reliability to observers that make observation reports.